2014
DOI: 10.18632/oncotarget.2609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of alternative splicing-derived hMENA isoforms in resected, node-negative, non-small-cell lung cancer

Abstract: Risk assessment and treatment choice remain a challenge in early non-small-cell lung cancer (NSCLC). Alternative splicing is an emerging source for diagnostic, prognostic and therapeutic tools. Here, we investigated the prognostic value of the actin cytoskeleton regulator hMENA and its isoforms, hMENA11a and hMENAΔv6, in early NSCLC.The epithelial hMENA11a isoform was expressed in NSCLC lines expressing E-CADHERIN and was alternatively expressed with hMENAΔv6. Enforced expression of hMENAΔv6 or hMENA11a increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…3A). As previously reported in different tumors, 10,14,19 WB with available antibodies (Fig. S3B) showed that Iso-11a (90 kDa protein) correlated with E-cadherin expression in HPDE, CFPAC and ASPC1.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…3A). As previously reported in different tumors, 10,14,19 WB with available antibodies (Fig. S3B) showed that Iso-11a (90 kDa protein) correlated with E-cadherin expression in HPDE, CFPAC and ASPC1.…”
Section: Resultssupporting
confidence: 84%
“…Our discovery that the pattern of hMENA isoforms may be a useful marker for early stage NSCLC, 10 suggested that this unique signature might also fill the lack of prognostic marker for pancreatic cancer. We explored the expression of hMENA isoforms in a series of surgically resected PDACs (n = 285), PanINs (n=15), chronic pancreatitis (n = 10), and normal pancreatic tissues from transplant donors (n = 3) (kindly provided by Lorenzo Piemonti, IRCCS San Raffaele Scientific Institute, Milan, Italy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the overexpression of hMENAΔv6, in the absence of hMENA 11a , increases vimentin and fibronectin overexpression as well as matrix metalloproteinase (MMP)2 secretion [68] (and unpublished results), all mesenchymal markers belonging to an EMT signature across various human cancers, as explored in The Cancer Genome Atlas (TCGA) [70]. In agreement, we have suggested that the pattern of hMENA isoforms may represent a powerful prognostic factor in NSCLC and pancreatic ductal adenocarcinoma (PDAC), hMENA 11a being a good and hMENAΔv6 a poor prognostic factor [67,68].…”
Section: Tme-related Mechanisms Leading To Mesenchymal Traits and Ressupporting
confidence: 57%
“…The actin cytoskeleton regulator hMENA (ENAH gene) has been found among the ESRP1/2 targets [64,65]. We have shown that the tissue-specific splicing program of Mena, with the switch from hMENA 11a to hMENAΔv6 isoform expression, may represent a crucial node in the convergence of EMT-related signaling pathways [66][67][68]. Transforming growth factor The convergence of tumor-intrinsic and -extrinsic factors, as above schematically illustrated, generates mesenchymal traits with immune cell exclusion and/or dysfunction involved in resistance to ICB treatments.…”
Section: Tme-related Mechanisms Leading To Mesenchymal Traits and Resmentioning
confidence: 99%